iMat:A Non-Intrusive and Low Cost Sleep Posture Estimation Mat - Singh, Ramandeep; Phutela, Nishtha; Jaisinghani, Dheryta (International Conference on Communication Systems and Networks (Online), 2024)
In this paper, we present sleep posture estimating mat - a specialized piece of technology designed to track and analyse various aspects of a person's sleep patterns during the night. These devices have gained popularity in recent years due to the growing interest in improving sleep quality and understanding sleep-related issues. The presented device makes use of human body capacitance to detect the sleeping position of the subject and gives valuable insights into the sleep patterns of the subject, ultimately helping them make informed lifestyle changes to achieve better sleep quality and overall well-being. It is non-intrusive as well as cost-effective. We successfully demonstrate operation of iMat for three sleep postures - Fetal, Log, and Soldier with an average estimation confidence of 70%.